2022
DOI: 10.2147/idr.s390881
|View full text |Cite
|
Sign up to set email alerts
|

Pubis Cryptococcal Osteomyelitis in an Immunocompetent Patient: A Case Report and Recent Literature Review

Abstract: Aim Skeletal involvement of Cryptococcus neoformans is rare and normally associated with disseminated cryptococcosis or potential predisposing factors. Here, we report an atypical case of osteoarticular cryptococcosis in an immunocompetent patient. Case Presentation We report a case of cryptococcal osteomyelitis in a 45-year-old female who presented with swelling and pain in the left inner thigh. After a biopsy of the pubic bone and surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Wang et al 17 reported disseminating a cryptococcal infection of the lumbar spine in an immunocompetent man who underwent surgical debridement combined with antifungal treatment. He et al 20 reported a case of pubis cryptococcal osteomyelitis in a 45-year-old female who drained pus by aspiration and oral fluconazole (400 mg/day) treatment. Our patient had no neurological impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 17 reported disseminating a cryptococcal infection of the lumbar spine in an immunocompetent man who underwent surgical debridement combined with antifungal treatment. He et al 20 reported a case of pubis cryptococcal osteomyelitis in a 45-year-old female who drained pus by aspiration and oral fluconazole (400 mg/day) treatment. Our patient had no neurological impairments.…”
Section: Discussionmentioning
confidence: 99%